1967
DOI: 10.1029/jz072i008p02099
|View full text |Cite
|
Sign up to set email alerts
|

Schroeter's rule and the modification of lunar crater impact morphology

Abstract: The 1∶1 correspondence of crater rim volume to true crater volume allegedly observed for many lunar craters has been explained previously by the theories of explosive meteoritic impact. In fact, the equality occurs too infrequently to be of genetic significance. The ratio characteristically is about 0.4 to 0.8 for small, freshly formed lunar and terrestrial craters, but it is well over 1.0 in older and larger lunar craters. Most of the moon's craters are of explosive impact origin and acquire a specific, predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

1972
1972
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“….7 .8 FRACTION OF EARTH COVERED BY BASINS volume of water and sea level has dropped from 2 to 1 km average depth (short dashed line). Impacts which produced basins 1000 km across also produced rim relief on those basins in excess of 1 km, if lunar cratering is any guide (Pike, 1967). Therefore the highest basin rims were above sea level when basins covered only 25% of the Earth's surface.…”
Section: Discussionmentioning
confidence: 97%
“….7 .8 FRACTION OF EARTH COVERED BY BASINS volume of water and sea level has dropped from 2 to 1 km average depth (short dashed line). Impacts which produced basins 1000 km across also produced rim relief on those basins in excess of 1 km, if lunar cratering is any guide (Pike, 1967). Therefore the highest basin rims were above sea level when basins covered only 25% of the Earth's surface.…”
Section: Discussionmentioning
confidence: 97%
“…(Only the ratios with the probable error lesser than the magnitude of the ratios themselves are considered here; N = 11.) Pike (1967) demonstrated that for the fresh crater Tycho (88 km), the Schroeter's ratio equals 1.99, rather than 0.80 predicted on the basis of Baldwin's (1963) work. Taken together, the quoted results, all resting on telescopic evidence, indicated that the diameter-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Application of any procedure that purports to monitor the crater degradation trends requires the knowledge of the initial crater geometry. In the case of the fresh simple craters whose linear dimensions are isometrically related (Pike, 1967) this is not a serious obstacle. For the present, let us adopt as a working hypothesis the notion that Croft's (1978) results for lunar craters hold for craters on all planetary surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…1971, Pike, 1967). On the other hand, in a hypervelocity impact event a tremendous compressional wave is produced.…”
mentioning
confidence: 99%
“…The prediction is that, with time, the crater floor will rise and the rim will sink until the entire structure approaches the original ground level (Danes, 1970 andPike, 1967 …”
mentioning
confidence: 99%